Simulation av Gulliver - En virtuell robotmiljö för skalade autonoma fordon - Dädeby, Sebastian; Eriksson, Adam; Khosravi, Pontus; Onsjö, Kristian; Sandell, Klas (My University, 2015)
Autonomous cars are the next step in the transportation sector in the hopes of reducing the environmental impact and increase safety, but they are expensive to develop and test. In order to facilitate the development and reduce test costs, a virtual test environment has been developed and tested via implementation of an autonomous steering function. In order to develop this virtual environment the simulation tool V-REP and the framework ROS were used, since both of these tools are developed for robot development. What has been developed is a virtual test environment as well as an interface for communication between simulation and framework. The result of this project is a virtual test environment where lters and steering algorithms can be calibrated and tested for usage in a physical environment, as well as support for the possibility of basic network communication between multiple cars. The virtual environment works well for testing the model. Simulator and framework have reached a functional level, but small errors occur which may demand further development to compensate for.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology